The concept of Islamic education in Indonesia in the postmodernism era - Mauliya Nandra Arif Fani; Muhamad Slamet Yahya; Windarwati Windarwati; Azizah Mega Yulianti; Ani Latifatul Nisa (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
The postmodernism movement is a new phase in the evolution of this era. Islamic education, particularly in Indonesian schools, confronts a number of challenges due to the postmodernism movement. Various problems experienced can come from internal or external. Therefore, this paper aims to analyze how the concept of Islamic education can be presented in the postmodernism period and how learning in the field of Islamic education faces it as an alternative for the next generation to remain superior humans beings. In this article, literature research is conducted with the description method, with the relevant books serving as sources and research materials, and Milles and Huberman data analysis techniques. In today's postmodernism, Islamic education must provide alternative learning to be in line with the era and always adjust to the progress of the era. Some alternatives in terms of education are applied in Islamic education learning. They are integrative religious education, multicultural education, gender equality-based education, religious moderation, and the role of teachers who are actively enganged in these solutions.